Epigenetic Repression of PDZ-LIM Domain-containing Protein 2: IMPLICATIONS FOR THE BIOLOGY AND TREATMENT OF BREAST CANCER - Qu, Zhaoxia (American Society for Biochemistry and Molecular Biology, 2010)
The NF-κB transcription factor plays a pivotal role in breast cancer progression and therapy resistance. However, the mechanisms by which the tightly regulated NF-κB becomes constitutively activated during breast cancer pathogenesis remain obscure. Here, we report that PDZ-LIM domain-containing protein 2 (PDLIM2), an essential terminator of NF-κB activation, is repressed in both estrogen receptor-positive and estrogen receptor-negative breast cancer cells, suggesting one important mechanism for the constitutive activation of NF-κB. Indeed, PDLIM2 reexpression inhibited constitutive NF-κB activation and expression of NF-κB-targeted genes in those breast cancer cells. Importantly, PDLIM2, but not its mutants defective in NF-κB termination, could suppress in vitro anchorage-independent growth and in vivo tumor formation of those malignant breast cells. In addition, we have shown that PDLIM2 repression involves promoter methylation. Accordingly, treatment of the breast cancer cells with the DNA methyltransferase inhibitor 5-aza-2′-deoxycytidine reverses the methylation of the PDLIM2 promoter, restored PDLIM2 expression, and suppressed tumorigenicities of human breast cancer cells both in vitro and in vivo. These studies thus provide important mechanistic insights into breast cancer pathogenesis. These studies also suggest a tumor suppression function of PDLIM2 and a therapeutic strategy for breast cancer.